Pengelolaan Arsip Digital - Sambas Ali Muhidin; Hendri Winata; Budi Santoso (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2016)
In a paper-based records management practices, many problems faced, so as to provide space in the electronic media as an alternative in the management of archives. In the terminology of archival, electronic media is classified as a new media archive. One new form of archive storage media is digital media. Digital media typically requires tools such as computers, because it can not be read directly. Archives are stored in digital form can include images, sound, video, text or any other that can be used as a data in binary form (binary), can be processed in a computer program and stored in a digital data storage media. Abstrak : Dalam praktik pengelolaan arsip berbasis kertas, banyak permasalahan yang dihadapi, sehingga memberikan ruang pada media elektronik sebagai alternatif dalam pengelolaan arsip. Dalam terminologi kearsipan, media elektronik dikelompokan sebagai arsip media baru. Salah satu bentuk penyimpanan arsip media baru adalah media digital. Media digital biasanya memerlukan alat bantu berupa komputer, karena tidak dapat dibaca secara langsung. Arsip yang disimpan dalam bentuk digital dapat berupa gambar, suara, video, tulisan atau lainnya yang dapat dijadikan sebuah data dalam bentuk biner (binary), dapat diolah dalam program komputer dan disimpan dalam media penyimpanan data digital.